Comparison of calcium carbonate versus calcium acetate in chronic kidney disease - Sonia Maqbool; Mohsin Raza (Medical Journal of South Punjab, 2025)
Objective: To compare the hypercalcaemic effect and phosphate binding power of calcium acetate and calcium carbonate in end-stage renal disease patients on maintenance haemodialysis.Methodology: This randomised control trial was conducted in four phases with calcium acetate or calcium carbonate. Sixty-four patients on haemodialysis were randomly divided into 2 groups. After a washout period of 2 weeks, each group was given calcium acetate or calcium carbonate for 2 months. After another washout period the patients were crossed over and again received these drugs for 2 months. Serum Calcium, phosphate, and albumin were analysed on Selectra E auto analyser at completion of each phase of study. Hypercalcaemic effect was defined as serum calcium >2.54 mmol/l, and phosphate binding power as serum phosphate